Retórica do silêncio e o silêncio da retórica: um enfoque sobre os atributos retóricos do silêncio na música de John Cage - Santos, Rodrigo Oliveira dos (2018)
This work aims to make a study about the ways of Cage to understand silence. Silence was already an usual practice in ancient music. Used in the word-painting technique in Renaissance music, with decorative purposes in relation to the text, in baroque music silence was used in a rhetorical way with the intention of moving the affections and persuading the listener to the emotion, as the figures of silence quite usual in the baroque period. The works of Bartel (1997), Cameron (2005), Gatti (1997), Lucas (2005, 2007, 2016) and Villavicencio (2011) were important points of interlocution in this perspective. The concept of imaginary was an important methodological element for establishing this comparison between silence in Baroque music and contemporary music by John Cage. From understanding the imaginary of Castoriadis (1992) and Durand (1998) we construct an understanding of the singularities as well as the interpretative connections between each of these silences: the rhetorical and intentional of baroque music and those of Cage's acasos and indetermination. In order to understand the silences of John Cage, a contextualization on Zen Buddhism was carried out in the United States at the end of the first half of the twentieth century, starting with Eco (1978), as well as a discussion of ideas of nothingness and emptiness in Zen, based on Heller (2011). Such a discussion is made in order to relate these ideas to concepts and questionings substantial to the understanding of silence in John Cage, such as ideas about nothingness, interpenetration, and the possibility of music, as an opening to the events of sounds to establish communication, and in that sense be rhetorical. Lacan's ideas about the symbolic and emptiness (1995, 2005) served as an element of understanding the limits and possibilities of Cage's silent project.